The destruction mechanism in GCTs - Lophitis, Neophytos; Antoniou, Marina; Udrea, Florin; Bauer, Friedhelm D.; Nistor, Iulian; Arnold, M.; Wikstrom, Tobias; Vobecky, Jan (My University, 2013)
This paper focuses on the causes that lead to the final destruction in standard gate-commutated thyristor (GCT) devices. A new 3-D model approach has been used for simulating the GCT which provides a deep insight into the operation of the GCT in extreme conditions. This allows drawing some conclusions on the complex mechanisms that drive these devices to destruction, previously impossible to explain using 2-D models. © 1963-2012 IEEE.
Keywords: Full wafer modeling; gate-commutated thyristor (GCT); maximum controllable current (MCC); safe operating area; thyristor